Age related changes to the dynamics of contralateral DPOAE suppression in human subjects - Konomi, Ujimoto; Kanotra, Sohit; James, Adrian L; Harrison, Robert V (Journal of Otolaryngology - Head & Neck Surgery, 2014)
The two ears are linked with a neural pathway such that stimulation of one ear has a modulating effect on the contralateral cochlea. This is mediated by cochlear afferent neurons connecting with olivo-cochlear efferents. The monitoring of this pathway is easily achieved by measuring contralateral suppression of otoacoustic emissions, and there is some clinical value in the ability to assess the integrity of this pathway. An important step in an evaluation of clinical utility is to assess any age-related changes. Accordingly, in the present study we measure the dynamics of contralateral DPOAE suppression in a population of normal hearing subjects of different ages. Using a real-time DPOAE recording method we assessed contralateral DPOAE suppression in 95 ears from 51 subjects (age range 2-52 years). DPOAE (2f1-f2; f2 = 4.4 kHz; f2/f1 = 1.22) input-output functions were measured. In response to contralateral broadband noise, dynamic aspects of DPOAE suppression were measured, specifically suppression onset latency and time constants. An age-related reduction in DPOAE amplitudes was observed. Both the detectability and the degree of contralateral DPOAE suppression were decreased in older age groups. We find an age-related increase in the latency of onset of DPOAE suppression to contralateral stimulation, but no significant change in suppression time-constants. Olivo-cochlear function as revealed by contralateral suppression of DPOAEs shows some important age-related changes. In addition to reduced emissions (outer haircell suppression) we find an increased latency that may reflect deterioration in auditory brainstem function. Regarding clinical utility, it is possible that the changes observed may reflect an aspect of age-related hearing loss that has not been previously considered.